Targeting p97 to Disrupt Protein Homeostasis in Cancer - Vekaria, Pratikkumar Harsukhbhai; Home, Trisha; Weir, Scott; Schoenen, Frank J.; Rao, Rekha (Frontiers in Oncology, 2016)
Cancer cells are addicted to numerous non-oncogenic traits that enable them to thrive. Proteotoxic stress is one such non-oncogenic trait that is experienced by all tumor cells, owing to increased genomic abnormalities and the resulting synthesis and accumulation of non-stoichiometric amounts of cellular proteins. This imbalance in the amounts of proteins ultimately culminates in proteotoxic stress. p97, or valosin containing protein (VCP) is an ATP-ase whose function is essential to restore protein homeostasis in the cells. Working in concert with the ubiquitin proteasome system, p97 promotes the retrotranslocation from cellular organelles and/or degradation of misfolded proteins. Consequently, p97 inhibition has emerged as a novel therapeutic target in cancer cells, especially those that have a highly secretory phenotype. This review summarizes our current understanding of the function of p97 in maintaining protein homeostasis and its inhibition with small molecule inhibitors as an emerging strategy to target cancer cells.